Can herbal products be alternative root canal irrigation solutions in primary teeth? An in vitro study. Issue 3 (December 2022) - Akgun, Semih Ercan; Arslan, Ipek; Aydinoglu, Sema; Gunacar, Dilara Nil; Alpay Karaoglu, Sengul; Yurteri, Emine; Suyabatmaz, Seyma
Abstract: Objectives: To evaluate antimicrobial properties and smear layer removal efficiency of various plant extracts and apple cider vinegar (AV). Methods: A total of 112 primary molars roots were randomly divided into two groups (n = 56) for antimicrobial test and infected with E faecalis and Candida albicans then divided again into 7 groups (n = 8) as physiological saline (PS), NaOCI, white tea (WT), Helichrysum arenarium (HA), AV, Citrus lemon (CL), and Anzer thyme (AT). Disinfecting abilities were measured with ImageJ. In the smear layer removal efficiency test, prepared 70 roots were divided into 7 groups (n = 10) as in the antimicrobial test also 2 subgroups were designed as with or without EDTA usage (n = 5). All samples were examined under SEM. Open dentin tubule percentage was evaluated with ImageJ. Results: HA and CL showed higher antibacterial activity against E. faecalis than PS (p = 0.038, p = 0.009) Antifungal activity of AV against C. albicans was higher than saline (p < 0.001). AV in the coronal third and CL in the middle third removed more smear layer than saline and NaOCI (p < 0.05). In the coronal region, HA and AV showed similar smear layer removal efficacy to NaOCl + EDTA (p > 0.05). CL, HA, and AV presented statistically similar results to NaOCl + EDTA in smear layer removal efficacy in the middle region (p > 0.05). Conclusions: CL and AV have antimicrobial efficacy against E. faecalis and C. albicans respectively and smear layer removal activity.